El Quijote: ese gran aburrido. Un método de incitación a la lectura - Sarrió Rubio, María Pilar (Didáctica. Lengua y Literatura, 2006)
The pedagogical interest that have the professors of Spanish Language and Literature by achieving that students read, has carried us to decide of applying a method of incitement to the reading having as motto: read The Quixote. In this I articulate we expose the part carried out during the first quarter of course, where we emphasize the great acceptance on the pat of the students and the appraisal that have done on this great work of Spanish Literature.
Keywords: The present time end modernity in The Quixote; Values of its reading; liberty and solidarity; Peace and contact